Testing an emotion regulation model of physical activity in adolescents with anorexia nervosa: A pilot ecological momentary assessment. (4th December 2019) - Kolar, David R.; Neumayr, Christina; Roth, Melina; Voderholzer, Ulrich; Perthes, Karin; Schlegl, Sandra
Abstract: Objective: Adolescents with anorexia nervosa (AN) often show increased levels of exercise and physical activity. Psychological models suggest that physical activity in AN might attenuate momentary negative affect. However, this has not been directly tested in adolescents with AN, and it remains unclear whether this is a distinct mechanism of physical activity in AN compared with healthy controls (HCs). Method: In a 1‐day ecological momentary assessment, 32 adolescent inpatients with AN and 30 HCs responded to hourly questions on momentary affect while wearing an actigraph to objectively assess physical activity. Results: Linear mixed models identified that adolescents with AN experienced more aversive tension, more negative affect, and less positive affect throughout the day than HCs. Preliminary evidence for a momentary association of higher levels of physical activity with positive affect were found for both groups, whereas higher levels of physical activity were associated with less negative affect in adolescents with AN only. When correcting for multiple testing, interactions did not hold statistical significance. Discussion: Our results indicate a down‐regulation effect of physical activity on negative affect for AN and a more general up‐regulation effect of positive affect. However, our sample size was small, and replication of our findings is needed.